The role of INDY in metabolism, health and longevity - Rogers, Ryan P.; Rogina, Blanka (Frontiers in Genetics, 2015)
Indy (I’m Not Dead Yet) encodes the fly homolog of a mammalian SLC13A5 plasma membrane transporter. INDY is expressed in metabolically active tissues functioning as a transporter of Krebs cycle intermediates with the highest affinity for citrate. Decreased expression of the Indy gene extends longevity in Drosophila and C. elegans. Reduction of INDY or its respective homologs in C. elegans and mice induces metabolic and physiological changes similar to those observed in calorie restriction. It is thought that these physiological changes are due to altered levels of cytoplasmic citrate, which directly impacts Krebs cycle energy production as a result of shifts in substrate availability. Citrate cleavage is a key event during lipid and glucose metabolism; thus, reduction of citrate due to Indy reduction alters these processes. With regards to mammals, mice with reduced Indy (mIndy-/-) also exhibit changes in glucose metabolism, mitochondrial biogenesis and are protected from the negative effects of a high calorie diet. Together, these data support a role for Indy as a metabolic regulator, which suggests INDY as a therapeutic target for treatment of diet and age-related disorders such as Type II Diabetes and obesity.